Merkostnader med vinterväghållning för Grot-transporter orsakade av väglagring. - Edmundsson, Jonathan (SLU/Dept. of Forest Resource Management, 2011)
Fuel wood is currently the third largest assortment from the forest in Sweden after pulpwood and lumber. Branches and tops i.e. logging residues are one of the assortments of fuel wood which is a common by-product after harvesting nowadays. The way to utilize, disintegrate and transport the logging residues varies between northern and southern Sweden. Branches and tops are collected throughout the year at appropriate stands, but are consumed mainly wintertime. The logging residues are usually stored at roadside along forest roads during the winter season until further transportation to the consumer is executed.